Ocean renewable energy in Malaysia: The potential of the Straits of Malacca - Chong, Heap Yih; Lam, W. (Elsevier Science Ltd, 2013)
The need for renewable energy is a global demand due to both the economic factors and the environmental concerns. Malaysian government has been supportive on the research and development in the renewable energies. Renewable Energy Act (2011) and Sustainable Energy Development Authority Act (2011) have been enacted to boost the industry of renewable energy. This paper presents the current status and future prospects of renewable energy in Malaysia with particular focus on the ocean renewable energy. Five types of ocean renewable energy were reviewed including tidal barrage, tidal current energy, wave energy, Ocean Thermal Energy Conversion (OTEC) and salinity gradient power. The comparison of various types of ocean renewable energy has been made to present their recent technologies in electricity generation. Tidal current energy is identified as a preferable option particularly in the Straits of Malacca.